Synthesis, XRD & SEM Studies of Heusler Ferromagnetic Shape Memory Alloys - Dhanal, S. V.; Kori, S. A.; Akkimardi, V. G.; Mokashi, M. S. (Asian Review of Mechanical Engineering, 2017)
Ferromagnetic Shape Memory Alloys (FSMAs) are the materials that responds to externally applied magnetic field similar to magnetostriction, but with vastly greater strain. These alloys are becoming an important element of sensor and actuator materials due to their large magnetic-field-induced strain and shape memory effect in recent years. In this work the structural parameters of relatively new Ni-Mn-Al and Ni-Mn-Sn Heusler FSMA were observed by X-Ray diffraction (XRD).In order to investigate the morphologies and microstructures of the inter layer matrix and filler of the prepared alloy, Scanning Electron Microscope (SEM) wasused for the observations. The alloy samples were prepared using vacuum arc melting technique. The average crystalline size was determined by using Scherrer equation.